1958
DOI: 10.1103/physrev.111.967
|View full text |Cite
|
Sign up to set email alerts
|

Hypernuclear Binding Energies and theΛ-Nucleon Interaction

Abstract: A phenomenological analysis is made of the binding-energy data for light hypernuclei in terms of a two-body A-nucleon interaction, in which account is taken of the empirical information available on the structure of light nuclei. It is found that the observed binding energies can be interpreted in terms of a spindependent A-nucleon interaction; the agreement obtained is adequate for any force-range between 0.4X 10~1 3 cm and 0.7X 10~1 3 cm (for Yukawa shape) and any exchange character for this interaction. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

1959
1959
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(20 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…Correspondingly, by including the ΛN-ΣN coupling explicitly, Miyagawa et al [6] performed the Faddeev calculations for 3 Λ H extensively to test these OBE potential models in this lightest system. They found that the ΛN-ΣN coupling is crucial to get the bound state of 3 He( 3 H)+Λ/Σ which was adopted originally by Dalitz and Downs [7], and then carried out the four-body coupled-channel calculation with the separable potentials of central nature [2]. J. Carlson tried to perform four-body calclation of these hypernuclei with NSC89 model by using Variational Monte Carlo method [3] and calculated the binding energies with statistical errors of 100 keV.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, by including the ΛN-ΣN coupling explicitly, Miyagawa et al [6] performed the Faddeev calculations for 3 Λ H extensively to test these OBE potential models in this lightest system. They found that the ΛN-ΣN coupling is crucial to get the bound state of 3 He( 3 H)+Λ/Σ which was adopted originally by Dalitz and Downs [7], and then carried out the four-body coupled-channel calculation with the separable potentials of central nature [2]. J. Carlson tried to perform four-body calclation of these hypernuclei with NSC89 model by using Variational Monte Carlo method [3] and calculated the binding energies with statistical errors of 100 keV.…”
Section: Introductionmentioning
confidence: 99%
“…(la) and (lc) can be tested in high-energy neutrino reactions, where they imply that, in the limit of infinite incident neutrino energy, the difference do-T (v+N)/dq 2 -do-T (v+N)/dq 2 approaches a constant which is independent of the leptonic invariant 4-momentum transfer q 2 . Bjorken, 3 by an isospin rotation, has transformed the neutrinoreaction results into inequalities on electron-nucleon (or muon-nucleon) scattering which hold in the limit of infinite incident electron energy; these inequalities may make it feasible to test Eq. (la) in the near future.…”
Section: (1c)mentioning
confidence: 99%
“…(6.8) is a variational wave function for the A-nucleus correlation: F (r) -exp (-air 2 )+C exp (-a 2 r 2 ) (6.10) whose parameters have been chosen to obtain the binding energy 44 i?A(AHe 4 ) = 2.33 MeV in the Gaussian potential well of the core nucleus with radius R w given by where R v = 0.904 is the range of a Gaussian potential of the same intrinsic range as a Yukawa potential of range (2/x) -1 . 45 The parameters in Eq. (6.10) have the values ai = 0.214 F~2, a 2 = 0.0384 F~2, and C= 0.339.…”
Section: The Initial Wave Functionmentioning
confidence: 99%